Prorok Daniel w jaskini lwów na reliefie z En Samsam w Golanie. Interpretacja przedstawienia - Szkołut, Paweł (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
The relief being a subject of this paper is carved on a basalt orthostat found reused in the village En Samsam, in Golan. The front of it has the lion’s shape. It suggest the orthostat’s primarly function as the base of the Tora shrine in a synagogue. In this case, the most probable synagogue was in En Nashut, which is situated only one kilometer from En Samsam. The orthostat could be dated between IV and the end of VI centuary. Nowadays, it is exibited in the Archaeological Museum of Golan, in Qatzrin. The research of the main scene of the relief was carried over in the broad context of its analogical representations in Jewish and Early Christian art. Supported by those and due to the Biblical histories and references, this scene is interpretated as howing the prophet Daniel in the lions’den - according to the Vl-th and XIV-th chapters of the Book of Daniel. Morever, the analisys of the reliefs motifs led to univeiling their symbolic background. The center of the scene is created by the human being standing between two lions and girded by a bell around his hips. His right hand is holding up the head of the lion. In a certain way this action symoblises the subdueing of the death. The prophet’s second hand is raised above the lioness with a suckling cub - symbolising here the life-giving fertility and the innocence. The scene with the man and lions is assisted by two eagles. One of them is holding a bunch of grapes in its beak. The symbolical meaning of the eagles is not synonimous here. But on the basis of the Bible, its apocrypha, the Rabbinic literature and the Jewish mystic tradition, they might refere to: the Divine providence and God’s protection, the angels and God’s messengers, the spiritual elevation and rejuvenalization, and finaly – the immortality. On this relief, the bunch of grapes shaped ovally as a wreath might be associated with the symbolism of salvation and immortality and on the other hand – with the idea of devoution and sacrifice. The red background of this scene might only strenghten the latter ones. While studing this scene and its symbolic value, one can distinguish several aspects of the hidden meaninigs. The prophet becomes here the symbol of the whole Israel as well, the nation struggling in its long history for the survival and suffering from the abversities es of fate. Israel faces here the threat of danger and death but due to the Lord’s providence the nation conquer it – hoping for the salvation in the history and eternity. The relief has also another symbolic significance considering Messiah. The analogy between the prophet Daniel and Messiah, described in the Bible especially in the Book of Isaja as the Lord’s Servant, might be discernible here. There, it is mentioned His sacriface for the human beings’ sake and His victory over death. It is the reason all symbols expressed on the relief through: lion, lioness with the cub, the eagles and grapes, might refere to Messiah and His mission. Suming up, the relief on the orthostat from the museum in Qatzrin, in Golan is an extremely interesting example of the narrative represantation in Jewish art. On its surface it depicts the historical prophet Daniel in the lions’ den, but in more profound layer it posses a symbolic power and significance refering to Israel and to Messiah as well. It is the reason, this represantation has the universal value for the Jewish and Chrisitian art. And it can be estimated as one of the most important monuments in ancient Jewish art.